Differential expression pattern, bioinformatics analysis, and validation of circRNA and mRNA in patients with arteriosclerosis - Liu, Yunyun; Wang, Kangjie; Li, Guanhua; Chen, Zhibo (Frontiers in Cardiovascular Medicine, 2022)
Background Lower limb arteriosclerosis obliterans (ASO) is the formation of atherosclerotic plaques in lower limb arteries, leading to vascular stenosis and occlusion, and is a major factor leading to lower limb amputation. The ASO seriously endangers the physical and mental health of patients. As living standards improve, the disease tends to occur in younger patients, and the incidence keeps increasing year by year. The circular RNAs (circRNAs) have been found to be tissue-specific, and they play an important role in a variety of diseases, but there are few studies on the pathogenic role and expression of circRNAs in ASOs. Method Three diseased arteries from patients with ASO and three healthy arteries from healthy donors were collected for second-generation sequencing, and the pathogenic pathways and possible pathogenic circRNAs related to ASO were screened through bioinformatics analysis. PCR and agarose gel electrophoresis were used to validate the sequencing results. The expression of circRNA-0008706 in human arterial smooth muscle cells (HASMCs) was knocked down using siRNA technology to explore its function. Result We identified 480 differentially expressed (DE) circRNAs and 2,997 DEmRNAs. Functional analysis revealed that epithelial-to-mesenchymal transition (EMT), lipid transport, regulation of extracellular matrix disassembly, regulation of cardiac muscle cell proliferation, branched-chain amino acid biosynthetic process, and positive regulation of cell growth and migration were enriched. Based on our previous microRNA array results, we constructed an ASO disease-specific competing endogenous (ceRNA) network. After validation, circRNA-0008706 was selected for functional analysis. Knockdown of circRNA-0008706 significantly suppressed the proliferation and migration phenotype of HASMCs and decreased the BCAT1 expression, which may be due to the specific binding of circRNA-0008706 to microRNA-125b-5p. Conclusion This study is the first to compare the circRNA and mRNA expression profiles of ASOs and healthy arterial specimens and to construct a disease-specific ceRNA network for ASOs. This study may provide a new therapeutic target for ASO.